Fractionated boiling technology: wort boiling of different lauter fractions - Yamashita, Hiroshi; Kühbeck, Florian; Hohrein, Alexander; Herrmann, Markus; Back, Werner; Krottenthaler, Martin (BrewingScience, 2006)
In the past few years, many innovations in wort boiling have been introduced in order to minimize thermal stress associated with the staling of beer. Many of these innovations were based on gentle wort boiling. These concepts were very successful for retaining beer flavor stability and saving energy. However, the possibilities are limited, because the quality of wort after lautering (sweet wort) itself cannot be altered. If sweet wort were separated into several groups according to each one’s staling sensitivity, it would be possible to achieve much more in the area of wort boiling. In the framework of this research, the first wort and the spargings were boiled separately. The first wort was treated as a staling-sensitive wort, and the spargings as a less staling-sensitive wort. No hops were added when boiling either the first wort or the spargings. The following was measured during boiling: extract, color, pH, polyphenols, nitrogen content and fractions, amino acids, carbohydrates, free dimethylsulfide (DMS) and carbonyl compounds. As a result of these investigations, distinct differences were observed between both of the boiled fractions, e.g. high amounts of substances resulting from lipid degradation in the boiled spargings. Additionally, the creation of different aroma compositions was possible through wort aroma simulations using Fractionated Boiling Technology (FBT). Some of these aroma components in wort are later important for the flavors typically associated with beer staling.